Overview and Recent Advances in Bioassays to Evaluate the Potential of Entomopathogenic Fungi Against Ambrosia Beetles - Jesús Enrique Castrejón-Antonio; Patricia Tamez-Guerra (Insects, 2025)
Ambrosia beetles, known for their symbiotic relationship with fungi cultivated within the tissues of host trees, have become significant pests, particularly when they serve as vectors for pathogenic fungi such as Raffaelea lauricola. Given the regulatory and environmental constraints for chemical application as a tool for their control, entomopathogenic fungi (EPF) represent a promising pest management alternative. This review presents an overview of bioassays assessing the pathogenicity and virulence of EPF against ambrosia beetles. Most studies have been performed in vivo (artificial diet) under laboratory conditions, focusing on exotic species and testing EPF genera such as Beauveria, Metarhizium, Isaria, and Purpureocillium. However, variations in inoculation methods, environmental conditions, and fungal formulations, have led to diverse results. In addition, the complex biology of these insects, particularly their dependence on symbiotic fungi, represents significant methodological challenges. Field trials (in situ bioassays) are still scarce, and there is a need to move toward standardized protocols and more objective experimental models that consider not only insects’ behavior but also ecological factors. Bridging this gap is essential for successfully implementing EPF-based strategies to assess ambrosia beetles’ biocontrol.